2009
DOI: 10.1038/ajg.2009.465
|View full text |Cite
|
Sign up to set email alerts
|

Complete Barrett's Eradication Endoscopic Mucosal Resection: An Effective Treatment Modality for High-Grade Dysplasia and Intramucosal Carcinoma—An American Single-Center Experience

Abstract: To our knowledge, this is the largest American single-center experience demonstrating that CBE-EMR with close endoscopic surveillance is an effective treatment modality for BE with HGD/IMC. Although the rate of stenosis development is significant, it is easily treated by endoscopic dilation. Patients considering endoscopic ablation should be counseled appropriately. The role of CBE-EMR in patients with lymphatic invasion or superficial submucosal invasion remains to be defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
159
0
14

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 227 publications
(178 citation statements)
references
References 56 publications
5
159
0
14
Order By: Relevance
“…Endoscopic resection has emerged as a promising treatment for HGD and early adenocarcinoma. [86][87][88][89] However, these methods are limited by disease recurrence, the frequent need for concurrent radiofrequency ablation, and ablation of the involved tissue. Endoscopic resection is also limited by the size of the nodule that can be removed, often requiring piecemeal resection and rendering histologic diagnosis difficult.…”
Section: Esophageal Diseasementioning
confidence: 99%
“…Endoscopic resection has emerged as a promising treatment for HGD and early adenocarcinoma. [86][87][88][89] However, these methods are limited by disease recurrence, the frequent need for concurrent radiofrequency ablation, and ablation of the involved tissue. Endoscopic resection is also limited by the size of the nodule that can be removed, often requiring piecemeal resection and rendering histologic diagnosis difficult.…”
Section: Esophageal Diseasementioning
confidence: 99%
“…In Japan, there are a few case reports about the complete eradication of ESD for BE including Barrett ' s esophageal cancer, but this treatment is not used generally because the risk of developing synchronous or metachronous lesions is very low in Japan ( 41 ). Th erefore, in Japan, it is considered that it might not require circumferential EMR ( 42,43 ) nor radiofrequency ablation ( 43 -45 ), which is performed in Western countries for BE AC, and the recurrence rates of SCC were signifi cantly higher than those of AC.…”
Section: Esophagusmentioning
confidence: 99%
“…However, the majority of these patients had IMC, whereas the rate of submucosal invasive cancer was decreased to 12.7 % (91). Subsequent studies from the surgical and endoscopic resection literature have reported even lower rates, between 4 % and 6.7 % (92,93).…”
Section: Endoscopic Therapies For Barrett Esophagusmentioning
confidence: 99%
“…1 and 2). furthermore, different studies have shown that staging by EMR can modify the previous biopsy diagnosis in up to 48 % of cases (93,102,103), which can dramatically change the clinical management of these patients, some of whom would be no longer suitable for endoscopic treatment due to histological evidence of submucosal invasion. Tumor staging using EMR pathology assessment is accurate when compared with surgical pathology, as shown in a study in 25 patients with HGD, IMC in Barrett's esophagus, where there was perfect agreement in T staging after EMR and esophagectomy (104).…”
Section: Endoscopic Mucosal Resection (Emr)mentioning
confidence: 99%
See 1 more Smart Citation